Effect Of Cellular Phone SMS As Health Education Media About HIV And AIDS On Health Service Search Behavior Of Women Sex Workers - Dewi Mahayani, Gusti Ayu Kade; Damayanti S, Made Rini; Utami, Putu Ayu Sani (Journal of A Sustainable Global South, 2022)
Abstract Human Immunodeficiency Virus (HIV) is a virus that attacks white blood cells (lymphocytes) that cause the decline of human immune. High risk groups such as Female Sex Workers (FSWs) tend not to access health services because of the decrimination they face in society. Health promotion is still an important strategy in increasing self-awareness of FSWs to perform Voluntary Counseling and Testing (VCT) examination, one of them is through the utilization of cellular phone technology. This study aims to determine the effect of cell phone Short Message Service (SMS) as a media health education about HIV and Acquired Immune Deficiency Syndrome (AIDS) to health seeking behavior of FSWs. Pre-experimental design one group pre-test pos-ttest design was conducted at 33 FSWs at Terminal Pesiapan, Tabanan District. The results of pre-test and post-test showed an influence on behavior (knowledge, attitude and action) after SMS based health promotion intervention (p <0,05), knowledge (p = 0,039), attitude (p = 0,003), and action (p = 0,000). After the intervention there was an increase in behavior that is on knowledge 30,3%, 36,4% attitude and 63,6% action. Mobile phone SMS media proves to be effective in conveying health information so as to raise awareness of FSWs in conducting HIV and Sexually Transmitted Infections (STIs). An innovative, short, easy-to-understand message on HIV and AIDS should be provided with simple language and regular use of cellular-based information technology by healthcare workers. Keywords: B ehavior, FSWs, H ealth E ducation, M obile P hone SMS